Studies on enzyme action V : Hydrolysis of isomeric glucosides and galactosides by acids and enzymes - Armstrong, Edward Frankland (1904)
As already pointed out, in studying the hydrolysis of sugars under the influence of enzymes, it is difficult to institute just comparisons, as not only, as a rule, is a different enzyme required for each sugar, but we have no means at present of determining the amount of enzyme used; and sooner or later, it will be necessary to accumulate data correlating one or more analytical factors (nitrogen percentage, etc.) with hydrolytic activity. The difficulty spoken of is enhanced by the fact that, usually, several enzymes occur together—so that no ordinary analytical process can suffice for the determination of the amount of a particular enzyme present in a solution.